Vigorous Orientation Signal Propagates Best from Collinear Motion. (May 2014) - Girelli, Massimo
In the present study, the Poggendorff illusion was tested with four types of stimuli: A moving dot, a moving bar parallel to the inducing lines, a moving bar collinear to the motion trajectory, and static bars as in the classic illusion. Psychometric functions of the alignment task showed that the collinear bar, where orientation and motion trajectory matched, yielded the best alignment performance almost eliminating the illusion; the vertical bar, on the contrary, showed the worst alignment, finally the dot and the static bars led to intermediate alignments. These results demonstrate the interaction between orientation and motion trajectory that likely takes place in the primary visual cortex (V1) where these two signals might be modulated by top-down activity from higher order areas such as the middle temporal (MT). This vigorous orientation-motion trajectory interaction allows extremely accurate positional predictions of moving objects in the visual scene, in particular during occlusion.